2008
DOI: 10.1557/proc-1107-101
|View full text |Cite
|
Sign up to set email alerts
|

Durability of a Cementitious Wasteform for Intermediate Level Waste

Abstract: Cementitious material is the most commonly used encapsulation medium for low and intermediate level radioactive waste. This paper focuses on the aqueous durability of a Materials Testing Reactor (MTR) cementitious wasteform -a possible candidate for the proposed intermediate level waste management facility in Australia. A series of medium term (up to 92 months) durability tests, without leachate replacement, were conducted on samples of this wasteform.The wasteform was made from cement, ground granulated blast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
2
2
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…Previous studies [1] showed the MTR samples to be characteristically white on the outside (to a depth of 800 µm) and mottled grey beneath the surface layer. XRF analysis showed the surface layer was richer in Na and K, and poorer in S and Ca than the bulk interior samples.…”
Section: Wasteform Materials and Sample Conditioningmentioning
confidence: 91%
See 1 more Smart Citation
“…Previous studies [1] showed the MTR samples to be characteristically white on the outside (to a depth of 800 µm) and mottled grey beneath the surface layer. XRF analysis showed the surface layer was richer in Na and K, and poorer in S and Ca than the bulk interior samples.…”
Section: Wasteform Materials and Sample Conditioningmentioning
confidence: 91%
“…This paper focuses on water transmission of a well-characterised candidate wasteform, one un-leached and the other leached for almost 8 years. In work already reported [1] a series of short to long term (up to 8 years) durability tests were conducted on this wasteform and the leaching tests were complemented by surface characterisation (using Scanning Electron Microscopy and Secondary Ion Mass Spectrometry) and bulk mineralogical analysis (X-ray Diffraction).…”
Section: Introductionmentioning
confidence: 99%
“…Whilst the cumulative findings of this research would indicate variable changes to barrier integrity, the influence of silica, from montmorillonite dissolution or from the cement and mortar itself, has yet to be fully explored. This is of particular importance because silica is both an important component of cementitious leachates [20] and has the capacity to form colloidal polymeric species at higher concentrations [21] which could induce macro-scale changes to the behaviour of clay minerals. To briefly summarise, the dissolution of silica in water involves hydration and dehydration reactions (catalysed by OH À ), forming monosilicic acid, which is inherently stable at concentrations of less than 100 ppm SiO 2 [21].…”
Section: Introductionmentioning
confidence: 99%